2019
DOI: 10.1016/j.athoracsur.2019.04.119
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Outcomes of Surgery for Invasive Valvular Endocarditis Involving the Aortomitral Fibrosa

Abstract: Background. Reconstruction of the intervalvular fibrosa (IVF) for invasive double-valve infective endocarditis (IE) is a technically challenging operation. This study presents the long-term outcomes of two surgical techniques for IVF reconstruction.Methods. From 1988 to 2017, 138 patients with invasive double-valve IE underwent surgical reconstruction of the IVF, along with double-valve replacement (Commando procedure, n [ 86) or aortic valve replacement with mitral valve repair (hemi-Commando procedure, n [ 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
66
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(72 citation statements)
references
References 16 publications
4
66
0
2
Order By: Relevance
“…With the imaging results of the brain MRI and cardiac CT, cardiac surgery evaluated the patient and estimated an approximately 40% operative mortality risk and determined that surgical intervention could not be safely offered. 6 After discussions with palliative care, the patient’s family decided to transition to comfort-oriented care. The patient subsequently died on hospital day 14.…”
Section: Case Reportmentioning
confidence: 99%
“…With the imaging results of the brain MRI and cardiac CT, cardiac surgery evaluated the patient and estimated an approximately 40% operative mortality risk and determined that surgical intervention could not be safely offered. 6 After discussions with palliative care, the patient’s family decided to transition to comfort-oriented care. The patient subsequently died on hospital day 14.…”
Section: Case Reportmentioning
confidence: 99%
“…The so-called "commando" or "hemi-commando" operations could be an option ( Figure 1A-D). Elgharably et al reported one-year survival of 91% and a 3-year survival of 82% when the hemi-commando procedure was performed, with recent additional information on the reconstruction of the aortomitral fibrosa in general with different techniques (27)(28)(29) . Moreover, such operations Review Article require long cardiopulmonary bypass, ischemic and overall operative times, which increase further the risk of postoperative complications.…”
Section: Contemporary Surgery For Endocarditismentioning
confidence: 99%
“…(B) The exposure following debridement of all infected tissue, removal of the aortic and mitral valves, and removal of the intervalvular fibrosa. Image courtesy of Navia et al4 Used with permission.…”
mentioning
confidence: 99%
“…The first step in the reconstruction, showing the mitral prosthesis sewn along the posterior two-thirds of the annulus. Image courtesy of Navia et al4 Used with permission.…”
mentioning
confidence: 99%
See 1 more Smart Citation